A metal-organic framework constructed by a viologen-derived ligand: photochromism and discernible detection of volatile amine vapors - Dong, Zhen-Peng; Zhao, Jiao-Jiao; Liu, Peng-Yu; Liu, Zhi-Liang; Wang, Yan-Qin (New journal of chemistry, 2019)
The detection of volatile amines has attracted great attention due to their high toxicity and widespread existence. Herein, we report a new example of a metal-organic framework (Co-MOF- 1 ) for the discriminative detection of alkylamines. Co-MOF- 1 that was assembled by Co( ii ), N 3 − and viologen-based ligand [H 2 L]Cl 2 ([1,1′-bis(4-carboxylatobenzyl)-4,4′-bipyridinium] dichloride) is a 3D cationic pcu framework with 1D channels containing electron-deficient viologen units, exhibits typical electrochemical redox properties and photochromic properties, and is involved in the radical formation via photoinduced electron transfer from nitrate ions and carboxylate groups in the channels to viologen moieties. More importantly, Co-MOF- 1 shows different color responses to different volatile amine vapors of different types and molecular sizes, which is attributed to the electron transfer from the amine to viologen. Moreover, the reason why Co-MOF- 1 can detect amines distinguishably is the different sizes of the substituents of the amine molecules and the number of N-H bonds of the amine molecules. Furthermore, the portable test paper was successfully prepared and provided a convenient and discernible detection of volatile amine vapors by depositing Co-MOF- 1 onto the filter paper, which can also be used as an erasable inkless printing medium. A Co( ii )-MOF based on a viologen-derived ligand was obtained: the Co( ii ) compound exhibits photochromism, and allows the visual and differentiable detection of different volatile alkylamines.